THROAT CANCER MONITORING DURING SPECIAL TREATMENT - I. Yu. Surovtsev; V. N. Korolev; K. I. Kulayev; K. S. Zuikov; A. S. Aladin (Опухоли головы и шеи, 2015)
The given paper attempts to objectify the course of a tumor process in patients diagnosed as having throat cancer during radiation or chemoradiation therapy. The authors propose a diagnostic algorithm which enables one not only to see the actual extent of a tumor, but also to estimate the degree of its resorption; hence, to more accurately plan special treatment and to timely change the treatment policy.